The Impact of Digital Marketing, Market Orientation, Entrepreneurial Competencies, and Entrepreneurship Characteristics on the Fashion MSMEs Performance in Yogyakarta - Siti Khusnul Rifani; Nina Fapari Arif; Riko Setya Wijaya; Fathi Habibatur Rahman (International Journal of Applied Business and International Management, 2025)
The creative economy sector has been a key driver of economic growth, with the fashion-textile and clothing industry being a significant component. However, businesses in this sector face numerous challenges as they strive to remain competitive within the MSME ecosystem. The objective of this study is to examine the impact of digital marketing, market orientation, entrepreneurial competence, and entrepreneurial characteristics on the performance of fashion SMEs in Yogyakarta. The research sample consists of 100 respondents, selected using maximum likelihood estimation. The methodology employed in this study is Structural Equation Modeling (SEM) with SMART PLS 3.2.9. The results indicate that digital marketing and market orientation have a significant positive effect on MSME performance, while entrepreneurial competence does not show a significant impact. Furthermore, entrepreneurial characteristics are found to enhance the performance of MSMEs. In conclusion, the findings highlight the importance of digital marketing, market orientation, and entrepreneurial characteristics in improving the performance of fashion SMEs, providing valuable implications for business strategies within this sector.